The trade description act 2011: regulating 'halal' in Malaysia - Zakaria, Z.; Ismail, S.Z. (2014)
Malaysia took its cue from the United Kingdom by passing the Trade Description Act in 1972. This act was to prevent manufacturers, retailers and service providers from manipulating and confusing consumers with false trade description and misleading conduct in the supply of goods and services. After 39 years in existence, it has now been repealed and replaced with the new Trade Descriptions Act of 2011. Enforced since 01 November 2011, salient changes have been made whilst maintaining its original objectives. One of the most significant features of the new Act is the creation of the Trade Description (Definition of Halal) Order 2011 and the Trade Description (Certification and Marking of Halal) Order 2011 giving specific legal proviso on matters pertaining to halal. This article discusses the Act and Orders and how are these provisions regulating halal in Malaysia.